Short notes on the Seismic Vulnerability of Greece under Austerity - Kassaras, I.; J. Sotirhos (Austin J Earth Sci., 2015)
This work presents the current state of seismic vulnerability in Greece, the most seismically active region in Europe and the corresponding impacts of austerity measures imposed to the nation during the last five years. The analysis of physical risks and socio-economic conditions shows a very dangerous situation, which has to be promptly confronted, in terms of a revised and prioritized National reinforcement effort regarding pre-seismic preparedness and post-seismic interventions. The latter certainly requires funding, however it has to be coupled with restorative measures for the existing socio-political status embracing authorities, communities and individuals.